2011
DOI: 10.1098/rsif.2010.0696
|View full text |Cite
|
Sign up to set email alerts
|

Bio-electrospraying and aerodynamically assisted bio-jetting the model eukaryotic Dictyostelium discoideum : assessing stress and developmental competency post treatment

Abstract: Bio-electrospraying (BES) and aerodynamically assisted bio-jetting (AABJ) have recently been established as important novel biospray technologies for directly manipulating living cells. To elucidate their potential in medical and clinical sciences, these bio-aerosol techniques have been subjected to increasingly rigorous investigations. In parallel to these studies, we wish to introduce these unique biotechnologies for use in the basic biological sciences, for handling a wide range of cell types and systems, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…In AABJ the cell suspension is drawn into a jet through an exit orifice by means of a pressure gradient subjected by way of a pressurized chamber over the exit orifice 11. This technology could be argued as being a softer approach for jetting cells for deposition, and indeed has been used for handling embryos 12, 13…”
mentioning
confidence: 99%
“…In AABJ the cell suspension is drawn into a jet through an exit orifice by means of a pressure gradient subjected by way of a pressurized chamber over the exit orifice 11. This technology could be argued as being a softer approach for jetting cells for deposition, and indeed has been used for handling embryos 12, 13…”
mentioning
confidence: 99%
“…From the demonstration of using this technology for both the processing of a wide range of advanced materials, spanning the structural and functional classes of materials, subsequent investigations established the ability for aerodynamically assisted jets to directly handle a wide range of cells and whole fertilized embryos. [33,34] The processed cells through this technology have undergone rigorous studies for assessing their viability and functionality from a molecular level upward, thus characterized via well-established biological protocols such as gene microarrays to those karyotypic studies. [34,35] Continued investigations have shown these post processed cells have been transplanted into mouse models, which have engrafted without rejection and thus have been comparable to those controls.…”
Section: Nonchannel/capillary Based Flow Cellsmentioning
confidence: 99%
“…[ 33,34 ] The processed cells through this technology have undergone rigorous studies for assessing their viability and functionality from a molecular level upward, thus characterized via well‐established biological protocols such as gene microarrays to those karyotypic studies. [ 34,35 ] Continued investigations have shown these post processed cells have been transplanted into mouse models, which have engrafted without rejection and thus have been comparable to those controls. [ 36 ] These studies together with our other investigations demonstrated AABJ’s capability to directly handle highly concentrated cellular suspensions.…”
Section: Flow Cell Technologymentioning
confidence: 99%
“…Townsend‐Nicholson and Jayasinghe showed that it was possible to directly electrospin living organisms under stable threading conditions by using a coaxial needle arrangement where a concentrated living biosuspension flowed through the inner needle and a medical grade poly(dimethylsiloxane) medium with high viscosity and low electrical conductivity flowed through the outer needle. This technique was employed to electrospin primary cells and whole organisms (e. g. Saccharomyces cerevisiae and Xenopus tropicalis ) that were viable over long periods of time . By employing a rotating mandrel as fibers collector for cell electrospinning, multiple core vessel‐like structures containing multiple cell types from the inner to the outer core were developed .…”
Section: Nano/microfibrous Scaffolds Fabricationmentioning
confidence: 99%